A new species of Calamaria (Squamata: Colubridae) similar to C. ceramensis de Rooij, 1913, from the Banggai Islands, east of Sulawesi, Indonesia - Koch, André; Arida, Evy; Mcguire, Jimmy A.; Iskandar, Djoko T.; Böhme, Wolfgang (Zootaxa, 2009)
A new species of reed snake, genus Calamaria, is described from the Banggai Islands off the east coast of Central Sulawesi, Indonesia. The new species, which is phenotypically similar to C. ceramensis from the central Moluccas, is characterised by the absence of preocular scales, five supralabials (third and fourth entering orbit), five infralabials (the first meet behind the mental), mental scale separated from the anterior chin shields, five scales surrounding the paraparietal, (most probably) seven modified maxillary teeth, a high number of ventral scales, a short, thick tail which is slightly tapering to a point, a single anal plate, as well as by a characteristic colour pattern of a pale brown dorsum dotted with darker spots, a pale collar behind the head, and a pale and dark lateral zigzag pattern along the body. Calamaria banggaiensis sp. nov. represents the fifty-eighth known species of Calamaria and the twelfth species of this genus recorded from the Sulawesi region. The new taxon is the only species of reed snake recorded from the Banggai Islands. It is known only from two adult specimens, a male and a female. For phenotypic comparison with the new species, both syntypes of C. ceramensis de Rooij, 1913, are depicted herein for the first time. An updated key to the Calamaria species of Sulawesi and its satellite islands is presented.